Land/Forest Use and Trends Analysis - MK16 Project Team (CGIAR Challenge Program on Water and Food, 2013)
The Land/Forest-use and Trends Analysis report assesses the land cover changes occurring in the TSB and Stung Pursat, describing as well the drivers of these changes. Furthermore, the report provides an overview of how forests are governed in Cambodia, and draws some recommendations and conclusions.